(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Avascular necrosis of the femoral head (ANFH) is a multifactorial disease in which local vascular disorders are closely associated with systemic metabolic, inflammatory, and endocrine changes. The most promising stage for active medical treatment is the initial stages of the disease, when there is no pronounced deformation of the articular surface, but mechanisms are already forming that determine further progression and reduced limb function. In this regard, it is of particular importance to study a complex of modifiable risk factors that can not only characterize the severity of the process, but also serve as guidelines for building targeted rehabilitation programs aimed at slowing down bone tissue destruction and stabilizing the clinical condition.